“The Crab Model” : Tips for Project Implementation at the Country Level - Hartwell, Christopher (World Bank, Washington, DC, 2012)
Project implementation at the country level relies not only on technical expertise and the soundness of a project, but on several external factors such as trust among the participating actors, political will, the absorptive capacity of a client government to actualize reform, and capacity within the government to implement reform. Any of these factors can stall or slow down the reform. To overcome this lack of capacity to reform, and to maintain continuous momentum, the author in Tonga has developed an approach to implementation that the author calls 'the crab model.'